Physiological demands of flat horse racing jockeys - Cullen, S.; O'Loughlin, G.; McGoldrick, A.; Smyth, B.; May, G.; Warrington, G. D. (The Journal of Strength and Conditioning Research, 2015)
The physiological demands of jockeys during competition remain largely unknown, thereby creating challenges when attempting to prescribe sport-specific nutrition and training guidelines. The purpose of this study was to evaluate the physiological demands and energy requirements of jockeys during flat racing. Oxygen uptake (VO2) and heart rate (HR) were assessed in 18 male trainee jockeys during a race simulation trial on a mechanical horse racing simulator for the typical time duration to cover a common flat race distance of 1,400 m. In addition, 8 male apprentice jockeys participated in a competitive race, over distances ranging from 1,200 to 1,600 m, during which HR and respiratory rate (RR) were assessed. All participants performed a maximal incremental cycle ergometer test. During the simulated race, peak VO2 was 42.74 ± 5.6 ml/kg/min (75 ± 11% of VO2peak) and below the mean ventilatory threshold (81 ± 5% of VO2peak) reported in the maximal incremental cycle test. Peak HR was 161 ± 16 b/min (86 ± 7% of HRpeak). Energy expenditure was estimated as 92.5 ± 18.8 kJ with an associated value of 9.4 metabolic equivalents. During the competitive race trial, peak HR reached 189 ± 5 b·min-1 (103 ± 4% of HRpeak) and peak RR was 50 ± 7 breaths per minute. Results suggest that horse racing is a physically demanding sport, requiring jockeys to perform close to their physiological limit to be successful. These findings may provide a useful insight when developing sport-specific nutrition and training strategies to optimally equip and prepare jockeys physically for the physiological demands of horse racing.